Specialist nurse in Europe: education, regulation and role. (12th September 2014) - Dury, C.; Hall, C.; Danan, J‐L.; Mondoux, J.; Aguiar Barbieri‐Figueiredo, M.C.; Costa, M.A.M.; Debout, C.
Abstract : Background: The concept of a 'specialist nurse' has existed for many years and related education programmes are proliferating. However, while literature clearly outlines the roles and practice of registered nurses and advanced practice nurses, those of specialist nurses remain unclear and nursing specializations across Europe need clarifying. Aim: This pilot study aimed to explore the competencies, education requirements and regulation of specialist nurses in Europe. Design: A descriptive cross‐sectional survey. Methods: An online questionnaire named 'Specialist nurse and specialization in Europe' was sent to 550 members of the European Federation of Nurse Educators and ten members of the European Specialist Nurses Organizations. Snowball sampling was then used to build a convenience sample of nurse educators, clinical nurses and specialist nurses, national nursing association members, and chief nursing officers from all European countries. Besides quantitative aspects, responses to open‐ended questions were analysed using a qualitative content analysis process. Results: A total of 77 experts from 29 European countries responded to the questionnaire. Findings highlighted variations in titles, levels and length of education, certification, regulation and scope of practice for specialized nurses in Europe. Analysis of the promoted competencies revealed dominant clinical and technical aspects of the role with a high level of knowledge. Conclusions: The study emphasized the need to improve standards for education, certification and regulation for specialist nurses. Interpretation of the role and competencies is diverse with a weak presence of health policy that would enhance and develop the specialities. Implications for nursing and health policy: To address the current lack of provisions for automatic recognition of specialist nurses, common training frameworks corresponding to the relevant level of the European Qualifications Framework should promote lifelong learning and mobility, and enhance levels of health care and patient safety.